Visualization of Traditional Urban Culture in the Lyrics of the Song 'Sesuatu di Jogja' by Adhitya Sofyan - Wibowo, Nimas (Airlangga University, 2024)
his research explores the portrayal of traditional urban culture in Yogyakarta through the narrative found in the song 'Sesuatu di Jogja,' narrated by Adhitya Sofyan. The song is believed to carry profound meaning in representing the traditional urban culture of the Yogyakarta region in urban studies in Indonesia. This study will employ textual analysis as its research method, considering that song lyrics are regarded as one of the various forms of text that possess diverse meanings depending on the communicator. By utilizing the semiotic approach from Ferdinand Saussure's perspective, this study will decipher the signifiers and signifieds within the lyrics of the song 'Sesuatu di Jogja.' The findings indicate that the song portrays the Yogyakarta region as a city of tourism, culture, history, and education, seen as the object of romance by the character in the song's lyrics. Additionally, Yogyakarta is narrated as a destination for tourists seeking tranquility away from the hustle and bustle of the capital city, Jakarta.